#TITLE_ALTERNATIVE# - (NIM 3229704), MUNIRWANSYAH
The development of infrastructure has been growing in Indonesia. Major factory has been constructed involving large-scale industries, including heavy machines. The infrastructures however, sometimes have to be located in difficult soils.. In addition, Indonesia is also surrounded by three major tectonic plates of the earth; Eurasian, Australian, and Pacific plates. Djoko Santoso (1978) observedthat the total number of earthquakes that occurred since 1897 with Magnitude equal to or larger than 4 Richter Scale is approximately 7500. Based upon the Directorate of Environmental Geology information, earthquake is one of the causes of heavy disasters in Indonesia. Maximum shear modulus is an important parameter in soil dynamics. This parameter is required in the analysis of dynamics of soils and foundations and soil-structure interaction during earthquake. This parameter is also needed in determining the effect of vibration coming from certain source and propagate to a sensitive structure nearby. The maximum shear modulus is used either in small strain or in large strain conditions. In the small strain condition, this modulus can be directly used, while if it is large strain, the modulus has to be determined by the other methode. Previous studies of determining the value of maximum shear modulus for clean sand or pure clay have been widely performed. Empirical formulas for predicting the value for clean sand or pure clay have also been developed. However, clean sand or pure clay in fact is rarely found in nature, moreover soil is frequently found in a combination of sandy and clayey soils. Sand commonly contains certain fine such as clay or silt in considerable amount and with different plasticity. Thus, it is not appropriate to determine the modulus of sandy clay or clayey sand by using empirical equations for clean sand only or pure clay only. In practice, this dynamic parameter is then predicted based upon correlations from the results of static tests that may be significantly different from that of proper dynamic tests. This study is therefore conducted to obtain empirical formula for predicting the maximum shear modulus of clay-sand mixtures by using a small strain resonant column and solid cylindrical sample under fixed-free condition. The modulus is determined based on the result of measured resonant frequency on soil column under certain dimension and weight.This research investigates the effect of fine content with different plasticity in sand-clay soils. Three different degrees of plasticity are used to represent different content of clay mineral. Soil samples consist of mixture between clean sand and fine content (clay and silt) with different water content. The content of clay and silt ranges from 90-10%, 80-20%, 70-30, ..., to 10-90% and the variation of water content are 10%, 15% and Wev. The soil samples then involve wide variety of plasticity and porosity. Theoretically, shear modulus is affected by confining pressure, porosity, plasticity and density. Therefore, the laboratory investigation was carried out on 3 different clayey soils with different plasticities. Each clay was mixed with sand in different fine contents. On each mixture three different water contents were applied at 10%, 15% and at the optimum moisture content. On each of them three different confining stress were applied. During earthquake or others dynamic loading, waves that travel through soil mass are propagated radially in every direction. To consider the effect of wave direction, soil samples prepared in mold are taken not only in the vertical but also in the horizontal direction. Therefore, this experiment involves more than 288 variations. During the experimental work with the resonant column, some tests had to be repeated due to the following the difficulties: first, samples were often consolidated faster before the resonant frequency is reached; second, samples are frequently found folded or bent up so that the resonant frequency could not be successfully determined; third, the sampling process at the fine content less than 10% was quite difficult and often collapsed, the installation of coil driver and accelerometer system was hard and was not so systematic that samples were often broken. Based on the experimental results, the effect of fine content on sand was optimum and resulted in maximum shear modulus when the fine content was 24%. This fine content is called as the optimum fine content. At that fine content the maximum shear modulus was found higher than that of either clean sand, pure clay, and mixed of clay and sand. For fine content that increased from 0% to 24%, the shear modulus also increase. Shear modulus will decrease if the increase of fine content was over 24%. Shear modulus also increase simultaneously in conjunction with the increase of the confining pressure, plasticity, density, and water content to optimum, but on the other hands itsorosity decreased. The different value of the modulus between vertical and horizontal Imples was less than 10%. In order to explain the experimental results, the inter-particle contact from Mindlin (1949)" theory is adopted. It is found that at the optimum fines content (24%), le width of slip-zone may reduce to approxcimatelly 50%. In order to obtain empirical formula for predicting the maximum shear modulus f clay-sand soil, 9 different curves adopting from the concept of shape function are westigated. For future research, it is suggested to investigate the dynamic properties f clayey-sand for different strain level; i.e. medium and large strains. It is also uggested to study typical relationships between threshold strains with shear modulus f clay-sand soil.